2022
DOI: 10.1186/s12951-022-01269-0
|View full text |Cite
|
Sign up to set email alerts
|

Unconjugated PLGA nanoparticles attenuate temperature-dependent β-amyloid aggregation and protect neurons against toxicity: implications for Alzheimer’s disease pathology

Abstract: Conversion of β-amyloid (Aβ) peptides from soluble random-coil to aggregated protein enriched with β-sheet-rich intermediates has been suggested to play a role in the degeneration of neurons and development of Alzheimer’s disease (AD) pathology. Aggregation of Aβ peptide can be prompted by a variety of environmental factors including temperature which can influence disease pathogenesis. Recently, we reported that FDA-approved unconjugated poly (d,l-lactide-co-glycolide) (PLGA) nanoparticles can have beneficial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 93 publications
1
21
0
Order By: Relevance
“…3 G). Consistent with earlier reports 29 , our results indicated that tau samples after 40 h incubation without heparin or Aβ seed demonstrated a random coil structure (random coil and others 91.1%, α-helix 2.6%, β-sheet 6.3%) with minima around 200 nm, indicating an absence of aggregate formation. In the presence of Aβ seed and heparin, tau exhibited a change in its conformation from a random coil to a predominant β-sheet structure (random coil and others 16%, α-helix 4.8%, β-sheet 79.2%) displaying minima around 216 nm with a faint shoulder peak at 222 nm.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…3 G). Consistent with earlier reports 29 , our results indicated that tau samples after 40 h incubation without heparin or Aβ seed demonstrated a random coil structure (random coil and others 91.1%, α-helix 2.6%, β-sheet 6.3%) with minima around 200 nm, indicating an absence of aggregate formation. In the presence of Aβ seed and heparin, tau exhibited a change in its conformation from a random coil to a predominant β-sheet structure (random coil and others 16%, α-helix 4.8%, β-sheet 79.2%) displaying minima around 216 nm with a faint shoulder peak at 222 nm.…”
Section: Resultssupporting
confidence: 93%
“…Apart from functionalized PLGA, we recently reported that PLGA nanoparticles without any drug/agent (i.e. native PLGA) can suppress Aβ aggregation/toxicity in cellular and animal models of AD 27 29 . However, no information is currently available if native PLGA can influence the aggregation, seeding or spreading of tau protein that acts synergistically with Aβ to trigger AD pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The data were collected without attenuation and a minimum number of 10 consecutive runs of 10sec each was averaged to obtain the autocorrelation function. Particle size was calculated by the manufacturer’s software through the Stokes–Einstein equation assuming spherical shapes of the particles [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…[ 273 ] Even with the temperature rising from 37 °C to 40 °C, the unconjugated PLGA nanoparticles still remain the ability to dissociate Aβ1‐42 aggregation. [ 274 ] Although the formation of PEG layers improves the stability of the delivered drug, the layers would reduce the drug encapsulation rate. Therefore, in response to this concern and the excellent curative effect of PLGAs, many studies have begun to encapsulate therapeutic AD drugs into PLGAs with organic or inorganic materials which have achieved rather considerable success in therapy recently.…”
Section: Low‐dimensional Nanomaterials For Alzheimer's Disease Treatmentmentioning
confidence: 99%